2020
DOI: 10.1111/tpj.15028
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive evolutionary pattern of organelle genomes linked to the nuclear genome in Selaginellaceae

Abstract: Plastids and mitochondria are endosymbiotic organelles that store genetic information. The genomes of these organelles generally exhibit contrasting patterns regarding genome architecture and genetic content. However, they have similar genetic features in Selaginellaceae, and little is known about what causes parallel evolution. Here, we document the multipartite plastid genomes (plastomes) and the highly divergent mitochondrial genomes (mitogenomes) from spikemoss obtained by combining short-and long-reads. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
60
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 30 publications
(66 citation statements)
references
References 105 publications
3
60
1
Order By: Relevance
“…So far, two hypotheses have been proposed: one is that disruptions to the nuclear-encoded, organelle-targeted DNA replication, recombination, and repair (DNA-RRR) systems are responsible for the unusual organellar genome evolution; the other is that the number of repetitive elements is positively associated with aberrant organellar genomes. DNA-RRR genes have been regarded as key players in organellar genome evolution (Kang et al, 2020;Weng et al, 2014). This opinion is stimulated mainly by the experiment results using mutants of model organisms (e.g., Arabidopsis and Physcomitrella) and bacteria addressing functions of RecA homologous and other genes of the DNA-RRR system (Cerutti et al, 1992;Cox, 2013;Odahara et al, 2009Odahara et al, , 2015Rowan et al, 2010;Shedge et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, two hypotheses have been proposed: one is that disruptions to the nuclear-encoded, organelle-targeted DNA replication, recombination, and repair (DNA-RRR) systems are responsible for the unusual organellar genome evolution; the other is that the number of repetitive elements is positively associated with aberrant organellar genomes. DNA-RRR genes have been regarded as key players in organellar genome evolution (Kang et al, 2020;Weng et al, 2014). This opinion is stimulated mainly by the experiment results using mutants of model organisms (e.g., Arabidopsis and Physcomitrella) and bacteria addressing functions of RecA homologous and other genes of the DNA-RRR system (Cerutti et al, 1992;Cox, 2013;Odahara et al, 2009Odahara et al, , 2015Rowan et al, 2010;Shedge et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This opinion is stimulated mainly by the experiment results using mutants of model organisms (e.g., Arabidopsis and Physcomitrella) and bacteria addressing functions of RecA homologous and other genes of the DNA-RRR system (Cerutti et al, 1992;Cox, 2013;Odahara et al, 2009Odahara et al, , 2015Rowan et al, 2010;Shedge et al, 2007). Kang et al (2020) reported a deficient DNA-RRR system in wild vascular plants and revealed the convergent evolution of plastome and mitochondrion genome (mitogenome) in Selaginellaceae caused solely by intact, dual-targeted recombinase gene. In studies on bacterial endosymbionts, it was reported that a deficient DNA-RRR system sometimes co-occurred with gene-order conservation (Garcia-Gonzalez et al, 2013;Tamas et al, 2002), or a highly dynamic architecture (Sloan & Moran, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…. Kang & al. (2020) illustrated the potential evolutionary mechanism leading to the unusual architecture and genetic content of chloroplast genomes within several Selaginella plants, which indicated that using chloroplast markers solely in the analysis of Selaginella could be problematic.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Selaginella pallidissima together with S. helvetica and a few similar species formed a monophyletic group in all molecular phylogenetic studies (Zhou & al., 2015b;Weststrand & Korall, 2016a). However, species delimitation within this group remained unclear, due to insufficient taxonomic sampling and inapplicability of molecular markers from the chloroplast genome, which was revealed to have high GC-biased nucleotide composition, elevated substitution rates, and complicated organization (Kang & al., 2020;. In previous studies, different individuals of the same species of this group clustered in various positions in the phylogeny due to incorrect identification or low differentiation of the markers (Zhou & al., 2015b;Weststrand & Korall, 2016a).…”
Section: ■ Introductionmentioning
confidence: 99%